Gambaran Mekanisme Koping Stres Pasien Diabetes Melitus Tipe II di Puskesmas Erwiri, Provinsi Maluku - Flawelna Falerery Pesulima; Yulius Yusak Ranimpi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Changes in the life of people with diabetes mellitus show negative psychological reactions such as anger, feeling useless, increased anxiety, and stress. This problem led to efforts to overcome it. This effort is called the coping mechanism. Both with problem focused coping and emotion focused coping. The purpose of this study was to describe the coping mechanisms of stress in patients with type II diabetes mellitus. This research was conducted at the Erwiri Health Center, South Buru Regency from September 2020 to November 2020. The research method used in this qualitative study was five participants. Data collection techniques through interviews and observation. The data validation technique uses data triangulation and data analysis using the model from Miles and Huberman. The results of the study found two coping functions and were grouped into 6 categories, namely: emotional focused coping consisting of self-control, positive reassessment, accepting responsibility, and running or avoiding, while problem focused coping consisted of seeking social support, and planning problem solving. . The conclusion of the coping mechanism carried out by the participants is emotional focused coping which consists of self-control by doing things that are liked and diverting the mind to positive things while reassessing positively by being grateful for what is experienced and doing routine treatment, accepting responsibility by remaining responsible for providing for the family and avoidance that is done in order to relieve stress, while problem focused coping is done is with social support obtained from family and friends, and problem solving is carried out with the initiative of each participant to overcome the stress that occurs. experienced.